Utility of MALDI-TOF MS for differentiation of Neisseria gonorrhoeae isolates with dissimilar azithromycin susceptibility profiles. (31st July 2020) - Pham, Cau D; Pettus, Kevin; Nash, Evelyn E; Liu, Hsi; St. Cyr, Sancta B; Schlanger, Karen; Papp, John; Gartin, Jarrett; Dorji, Tandin; Akullo, Kaidee; Kersh, Ellen N; ,
Abstract: Background: Antibiotic-resistant gonorrhoea has been a chronic public health burden since the mid-1930s. Recent emergence of isolates resistant to the current recommended antibiotics for gonorrhoea further magnifies the threat of untreatable gonorrhoea. The lack of new, effective antibiotics highlights the need for better understanding of the population structure of Neisseria gonorrhoeae in order to provide greater insight on how to curtail the spread of antimicrobial-resistant N. gonorrhoeae . Objectives: To explore a potential application of MALDI-TOF MS to differentiate N. gonorrhoeae displaying different levels of susceptibility to the antibiotic azithromycin. Methods: We conducted MALDI-TOF MS using the Bruker Biotyper on 392 N. gonorrhoeae isolates collected through the Gonococcal Isolate Surveillance Project (GISP) and/or the Strengthening the United States Response to Resistant Gonorrhea (SURRG) project. The MALDI-TOF MS spectra were visually analysed to assess the presence of distinctive peak(s). Statistical analysis was performed to assess the relationship between gonococcal isolates with the distinct protein peak and antibiotic susceptibility. Results: In this study, we were able to differentiate N. gonorrhoeae isolates into two distinct subpopulations using MALDI-TOF MS. Isolates were distinguished by the presence or absence of a spectral peak at 11 300 Da. Notably, these two groups exhibited different levels of susceptibility to azithromycin. Conclusions: We have shown that in addition to its ability to identify N. gonorrhoeae, MALDI-TOF MS could also be used to differentiate gonococcal isolates with different levels of susceptibility to azithromycin.